Neuroprotective effect of remote ischemic preconditioning in patients undergoing cardiac surgery: A randomized controlled trial - Zhu, Shouqiang; Zheng, Ziyu; Lv, Wenying; Ouyang, Pengrong; Han, Jiange; Zhang, Jiaqiang; Dong, Hailong; Lei, Chong (Frontiers in Cardiovascular Medicine, 2022)
Background: The neuroprotective effect of remote ischemic preconditioning (RIPC) in patients undergoing elective cardiopulmonary bypass (CPB) assisted coronary artery bypass graft (CABG), or valvular cardiac surgery remains unclear. Methods: A randomized, double-blind, placebo-controlled superior clinical trial was conducted in patients undergoing elective on-pump coronary artery bypass surgery or valve surgery. Before anaesthesia induction, patients were randomly assigned to RIPC (three 5-minute cycles of inflation and deflation of blood pressure cuff on the upper limb) or the control group. The primary endpoint was the changes in S-100 calcium-binding protein β (S100-β) levels at 6 hours postoperatively. Secondary endpoints included changes in Neuron-specific enolase (NSE), Mini-mental State Examination (MMSE), and Montreal Cognitive Assessment (MoCA) levels. Results: A total of 120 patients (mean age, 48.7 years; 36 women [34.3%]) were randomized at three cardiac surgery centers in China. One hundred and five patients were included in the modified intent-to-treat analysis (52 in the RIPC group and 53 in the control group). The primary result demonstrated that at 6 hours after surgery, S100-β levels were lower in the RIPC group than in the control group (50.75; 95% confidence interval, 67.08 to 64.40 pg/ml vs. 70.48; 95% CI, 56.84 to 84.10 pg/ml, P = 0.036). Compared to the control group, the concentrations of S100-β at 24 h and 72 h, as well as the concentration of NSE at 6h, 24h and 72 h after surgery were significantly lower in the RIPC group. However, neither the MMSE nor the MoCA revealed any significant between-group differences in terms of cognitive function at 7 days, 3 months and 6 months after surgery. Conclusions: In patients undergoing CABG or valve surgery, RIPC attenuated brain damage as indicated with the decreased release of brain damage biomarker S100-β and NSE. Trial registration number ClinicalTrials.gov, NCT01231789